The Impact of Corporate Reputation on Brand Attitude and Purchase Intention: A Case of Kathmandu Valley - Rai, Anjana; Sah, Puja (Nepalese Journal of Business, 2025)
This study examines the brand attitude and purchase intention of customers through the corporate reputation in Kathmandu valley. Brand attitude and purchase intention are selected as the dependent variable. Similarly, perceived quality, online review, corporate social responsibility, social media influencer and image of executive officer are selected as the independent variables. This study is based on primary data with 122 observations. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of different factors influencing corporate reputation in Kathmandu valley. The study showed that perceived quality has a positive impact on customer brand attitude and customer purchase intention. It means that increase in perceived quality leads to increase in customer brand attitude and customer purchase intention. Similarly, online review has a positive impact on customer brand attitude and customer purchase intention. It indicates that increase in online review leads to increase in customer brand attitude and customer purchase intention. Moreover, corporate social responsibility has a positive impact on customer brand attitude and customer purchase intention. It means that increase in corporate social responsibility leads to increase in customer brand attitude and customer purchase intention. Likewise, social media influencer has a positive impact on customer brand attitude and customer purchase intention. It shows that increase in social media influencer leads to increase in customer brand attitude and customer purchase intention. Furthermore, image of executive officer has positive impact on customer brand attitude and customer purchase intention. It shows that higher the image of executive officer, higher would be the customer brand attitude and customer purchase intention.